Implementation of justice Related to Discrimination Against Women in the Form of Sexual Harassment According to Law No. 39 of 1999 - Rasji Rasji; Agatha Augustin; Lena Mariana Sitorus (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The issue of gender is common, and long ago the injustices against women have been simulated. Women often become objects of violence, both physically and psychologically. Women become objects of sexual exploitation and violence. Therefore, Indonesia as a country of the law based on pancasila, has an obligation to provide gender justice and protection against women. As a form of protection, Indonesia has passed legislation related to efforts to provide justice and protection against women, the bill on human rights. With the regulation introduced in Indonesia, it is expected to provide gender justice and protection against women.